The role of short-chain fatty acid metabolism in the pathogenesis, diagnosis and treatment of cancer - Hou, Maolin; Yu, Qing-Qing; Yang, Le; Zhao, Haibo (Frontiers in Oncology, 2024)
Short-chain fatty acids (SCFAs), which are saturated fatty acids consisting of six or fewer carbon atoms, have been found to be closely associated with the biological behavior of malignant tumors. This manuscript provides a comprehensive review on the role of SCFAs in regulating cell cycle, apoptosis, tumor angiogenesis, epithelial-mesenchymal transition, protein regulatory pathways, and histone regulation in promoting the development of malignant tumors. Furthermore, we discuss the potential therapeutic strategies targeting SCFAs for treating malignant tumors. This review offers a theoretical foundation for investigating the mechanisms by which SCFAs impact malignant tumors and provides insights into developing novel treatment targets.